Information for contributors and readers for issue 4-2016 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2016)
DOAJ Seal awarded to the Military Technical Courier SHERPA/RoMEO Database has coded the archiving policy of the Military Technical Courier according to the category: “Green RoMEO color”